The Protective Role of GMI, an Immunomodulatory Protein From Ganoderma microsporum, on 5-Fluorouracil-Induced Oral and Intestinal Mucositis. (March 2019) - Li, Che-Hsing; Ko, Jiunn-Liang; Ou, Chu-Chyn; Lin, Wea-Lung; Yen, Cheng-Chieh; Hsu, Chih-Ting; Hsiao, Yu-Ping
5-Fluorouracil (5-FU) is used in the treatment of head and neck cancer patients. However, adverse effects experienced such as mucositis and poor appetite may lead to interruption in chemotherapy. The aim of this study is to evaluate the efficacy of GMI, one fungal immunomodulatory protein found in Ganoderma microsporum, for mucositis induced by 5-FU in a mouse model. Mice were administered 5-FU intraperitoneally for 4 days per cycle for a total of 2 chemotherapy cycles. In addition, mice were pretreated with GMI or phosphate-buffered saline 3 days before 5-FU intraperitoneal injection and daily until day 14. On histological analysis, GMI prevented 5-FU-induced damage to the intestinal mucosa and tongue epithelium. We also demonstrated that GMI enhanced the cytotoxicity of 5-FU in 2 oral cancer cell lines, while GMI could not promote this effect in an oral normal cell. In conclusion, GMI alleviates 5-FU-induced damage and decelerates cell death in normal alimentary tract tissue.